Predictors of behavioral intention among tourist: the case of revisiting street food spots in Penang, Malaysia. Issue 4 (4th July 2022) - Mohamad, Noraihan; S.Palan, Devandran; Roslan, Muhammad Aidil; Nasron, Nurul Aizat
ABSTRACT: Penang is a popular destination among both local and international visitors where its street food is a major attraction. The uniqueness of Penang's street food contributes to its reputation as a food paradise among tourists. However, studies investigating tourists' perception of Penang street food and their behavioral intention to revisit Penang street food spots remain scarce. Thus, a case study involving 277 valid responses was designed to explore this phenomenon by identifying the main factors influencing tourist behavioral intention in revisiting Penang street food spots. Findings demonstrated that 47.4% of the variance in behavioral intention is influenced by food hygiene, food price, food quality and service quality. Furthermore, the food service quality is reported to significantly influence tourist behavioral intention in revisiting Penang street food, while hygiene and price are insignificant in this respect. The current study extends the body of knowledge concerning tourist behavioral intention in revisiting street food, thereby providing useful recommendations and important information to both food hawkers and local authorities alike.